2017
DOI: 10.4317/jced.53732
|View full text |Cite
|
Sign up to set email alerts
|

Traction test of temporary dental cements

Abstract: BackgroundClassic self-curing temporary cements obstruct the translucence of provisional restorations. New dual-cure esthetic temporary cements need investigation and comparison with classic cements to ensure that they are equally retentive and provide adequate translucence. The objective is to analyze by means of traction testing in a in vitro study the retention of five temporary cements.Material and MethodsTen molars were prepared and ten provisional resin restorations were fabricated using CAD-CAM technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The specimens were then used in a trial of complete coverage CAD-CAM provisional restorations, which set out to evaluate the retention of five temporary cements ( 10 ). Each study group (n=10) used the same ten specimens to perform a total of 50 tensile tests; these used ten CAD-CAM provisional restorations bonded with each of the five temporary cements to the ten identically prepared molars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens were then used in a trial of complete coverage CAD-CAM provisional restorations, which set out to evaluate the retention of five temporary cements ( 10 ). Each study group (n=10) used the same ten specimens to perform a total of 50 tensile tests; these used ten CAD-CAM provisional restorations bonded with each of the five temporary cements to the ten identically prepared molars.…”
Section: Resultsmentioning
confidence: 99%
“…It permits different designs adapted to both complete and partial coverage restorations (inlays, onlays, overlays and endocrowns). In studies of temporary cements, the specimens can be reused ( 10 ) but of course this is not possible in studies of definitive cements or bonding techniques on teeth. When natural teeth are used, the researcher can carry out different bonding techniques, which notably influence the behavior of the materials under investigation ( 1 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we endeavored to manufacture a specimen using a standardized method by preparing natural teeth in a certain abutment shape with a tooth standardization technique using CAD/CAM technology. This method can accurately replicate different teeth in the same form and use natural properties—such as wettability, thickness, and the pulp pressure of dentin—that cannot be imitated in artificial materials [ 37 , 38 ]. In addition, it has been reported that the thermal cycling treatment performed on a specimen can obtain an effect resembling the body aging process as if it were a natural specimen [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also dual-cure temporary cements that are considered translucent resins. 14 Cements should provide sufficient adhesion and sealing properties and should not be affected by fluids in the oral cavity. When removing restorations, it is preferable for the cements to remain on the restoration rather than the tooth, and for them to be easy to clean outside of the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…When removing restorations, it is preferable for the cements to remain on the restoration rather than the tooth, and for them to be easy to clean outside of the mouth. 14 This is why it is important to choose temporary cements that bond well to the restoration but have a weaker bond to the dentin. This helps to reduce the time spent with the patient during the trying on session.…”
Section: Introductionmentioning
confidence: 99%